Estercos de bovino e de frango no estabelecimento e desenvolvimento do cajueiro-anão - Costa, Luilson Pinheiro (2019)
The application of organic fertilizers in the planting hole is a recommended practice for most pereniza crops, as it promotes the improvement of soil attributes and is a source of plant nutrients. However, for the cashew crop, little is known about the effects of the application of organic fertilizers in the hole planting pit on the initial development of the plant. Therefore, the objective of this study was to study the effects of cattle and broiler manure doses during the establishment and development of 'BRS 226' dwarf cashew under field conditions. The experiment was carried out in the Pacajus Experimental Field, belonging to Embrapa Tropical Agroindustry, located in the city of Pacajus/Ceará, and conducted for thirteen months, covering one month of reaction of the inputs in the pit soil and twelve months of cultivation. The experimental design was in randomized blocks, in a 2x5x2 factorial arrangement, with two sources of manure (cattle and chicken), five doses (0; 5; 10; 15 and 20 L per pit) and two soil sampling times (at planting and 365 days after planting), with four repetitions. Each experimental unit consisted of six dwarf cashew plants. The evaluations began by monitoring the pit soil temperature during the reaction period of the inputs, and continued with the characterization of the chemical attributes of the pit soil until the end of the experiment. The development of early dwarf cashew plants was also evaluated by determining plant height, stem diameter and crown volume. In addition, freshly harvested leaves were collected to evaluate the nutritional status of the cashew trees. The obtained data were subjected to analysis of variance by the F test and the doses compared by regression analysis. To compare the sources of organic fertilizer we used the Tukey test at 5 % probability. It was observed that application of cattle manure doses between 8.5 and 9.1 L by planting hole increased the development of 'BRS 226' dwarf cashew plants in the field, while chicken manure should not be applied in the planting hole of cashew trees 'BRS 226'.